Role of Steindler Elbow Flexorplasty in Change of Movement at Elbow Joint in Traumatic Brachial Plexus Injuries (Journal of Pakistan Orthopaedic Association, 2016)
Objective: To restore the elbow function; the wrist arthrodesis if needed proceeded before Steindler flexorplasty and finally sahaâ€™s procedure to restore shoulder abduction in neglected brachial plexus injuries.Methods: We conducted a quasi-experimental study of fifteen patients with absent or extremely weak elbow flexion (motor grade 2 or less) due to traumatic brachial plexus injuries (C5-C6-C7/C5- C6 deficit), which had undergone surgical reconstruction of the flail elbow by tendon transfer (Steindler elbow flexorplasty). The etiology of elbow weakness in all patients was traumatic brachial plexus palsy (C5-C6-C7/C5-C6 deficit) between 2011 to 2014. Elbow flexion improved or not improved measured in term of range of motion at elbow joint. Age, gender, preoperative strength (rated on a 0 to 5 scale for the flexors of the elbow and wrist flexors), previous surgery, length of follow-up, other associated operative procedures, results and complications were recorded.Results: Average age of the patients was 23.2% while Percentage of male patients were 86.66% and female patients were 13.33%. The percentage of C5-C6 palsy was 86.66% while average time elapsed since injury was 20.5 months. We followed the patients on average of 1.75 years . The Percentage of very Good Patients is 66.66% and good is 20%. Our few Patients developed complication but these complications were managed effectively.Conclusion: Steindler Elbow Flexorplasty is good and effective procedure in improving the range of motion (Change) at elbow joint in traumatic brachial plexus injuries (C5-C6-C7/C5-C6 deficit).Key Words: Steindler Elbow Flexorplasty, Traumatic, Brachial Plexus Injuries